The Effect of Work Experience and Organizational Culture on Employee Productivity through Job Satisfaction as an Intervening Variable at Company: Pengaruh Pengalaman Kerja dan Budaya Organisasi terhadap Produktivutas Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening pada Perusahaan - Putri, Dini Anggaita; Sumartik (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study was to determine the effect of work experience and organizational culture on employee productivity at PT. Implora Sukses Abadi with employee job satisfaction as an intervening variable. In determining the number of samples in this study, the Porposive Sampling . formula was used so that the number of samples used in this study were 134 respondents. Data analysis technique used is path analysis. The data collection technique used in this study was to distribute questionnaires and the tools to analyze the data obtained were using IBM SPSS Statistics 25 for windows. The results obtained from this study prove that that 1) Work Experience has a significant influence on Employee Productivity. 2) Organizational Culture has a significant influence on Employee Productivity 3) Work Experience has a significant influence on Job Satisfaction. 4) Organizational Culture has a significant influence on Job Satisfaction. 5) Work Experience has a significant influence on Employee Productivity through Job Satisfaction. 6) Organizational culture has a significant influence on employee productivity through job satisfaction.7) Job Satisfaction has a significant effect on Employee Productivity